Evaluation of Adverse Drug Reactions in Paediatric Patients: A Retrospective Study in Turkish Hospital - Khan, Zakir; Karataş, Yusuf; Kıroğlu, Olcay (Frontiers in Pharmacology, 2021)
Drug safety in paediatric patients is a serious public health concern around the world. The paediatric patients are more prone to adverse drug reactions (ADRs) than adults. Moreover, there is a scarcity of information about ADRs in paediatric patients. This study was conducted to determine the frequency, causality, severity, preventability of paediatric patients' ADRs reported in a tertiary care hospital in Adana, Turkey. A retrospective study was conducted on all spontaneously reported ADRs between January 01, 2020, to July 30, 2021, in paediatric patients. The ADRs reports were evaluated in terms of gender, age, ADR characteristics, suspected drugs and reporting source. All included ADRs reports were characterized according to the Naranjo Algorithm/World Health Organization (WHO) causality scales, Hartwig/Siegel and Common Terminology Criteria for Adverse Events (CTCAE) severity scales, the modified Schoumock and Thornton preventability scale and hospital pharmacovigilance center criteria for seriousness. Therapeutic groups were also coded using the WHO-Anatomical Therapeutic and Chemical (ATC) classification. During the study period, 8912 paediatric patients who were admitted had 16 ADRs with 1.7 ADRs/1,000 admissions. The majority of ADRs were found in infants (31.2%) and children (56.2%) as compared to adolescents (12.5%). ADRs were observed more in females (81.2%) than males. Skin (62.5%) was the most affected organ due to the ADRs, and maculopapular rash and erythema multiforme were the most commonly reported symptoms. Most ADRs were probable/likely (93.7%), severe (50%), preventable or probably preventable (43.7%) and serious (37.5%). Antibiotics (93.7%) were found to be the most common cause of ADRs in paediatric patients. The majority of ADRs were associated with vancomycin (68.7%). Most of the ADRs were reported by a medical doctor in this study. This small sample size study highlights significant problems of ADRs in paediatric patients, mainly caused by antibiotics and with a majority of ADRs manifest as skin reactions. Furthermore, a high proportion of the identified ADRs were found to be preventable. More focused efforts are needed at the national level to avoid preventable ADRs in hospitals. Monitoring and management of ADRs and future studies would be beneficial for better patient care and safety.